Potential Utility of School‐Based Telehealth in the Era of COVID‐19. (5th May 2021) - Williams, Stormee; Xie, Luyu; Hill, Kristina; Mathew, Matthew Sunil; Perry, Tamara; Wesley, Danielle; Messiah, Sarah E.
ABSTRACT: BACKGROUND: The COVID‐19 pandemic presents unique opportunities for preexisting school telemedicine programs to reach pediatric populations that might otherwise experience a lapse in health care services. METHODS: A retrospective analysis of one of the largest school‐based telemedicine programs in the country, based in the Dallas‐Fort Worth (DFW), Texas was conducted that included 7021 pediatric patients who engaged in telehealth visits from 2014 to 2019. RESULTS: Asthma or other respiratory disease was the primary diagnosis (28.4%), followed by injury or trauma (18.4%), digestive disorders (6.9%), and ear/eye/skin disease (6.9%). More participants were from the North (34.4%) and West (33.2%) ISD compared to the South (20.6%) and East (11.7%) schools. Likewise, the majority of COVID‐19 cases were in the North (61.8%) and West (31.6%) DFW regions, leading to 989 (59.9%) and 551 (33.4%) deaths, respectively. CONCLUSIONS: School‐based telehealth programs have the potential to reach large pediatric populations most in need of health care due to COVID‐19‐related lapses in services, and to address COVID‐19‐related health issues as schools reopen. In the future, utilization could be expanded to contact tracing, testing, and screening for COVID‐19.